The economics of football - Dobson, Stephen (Cambridge University Press, 2001)
An original economic analysis of professional football. Uses theoretical and empirical methods to consider role of owners, managers, players and spectators. Concludes with an extended discussion of key policy issues, including European super league proposals, contractual arrangements in the players' labour market, and football's evolving relationship with the broadcasting media.
Keywords: Soccer -- Economic aspects -- Great Britain.; Soccer -- Great Britain -- Finance.; Football -- Aspect économique -- Grande-Bretagne.; Football -- Grande-Bretagne -- Finances.; BUSINESS & ECONOMICS -- Industries -- General.; Soccer -- Economic aspects; Soccer -- Finance; Great Britain; Samfundsvidenskab -- Økonomi.; Electronic book.; Electronic books.